Patient And Nurse Experience Of Using Somatostatin Analogues To Treat Gastroenteropancreatic Neuroendocrine Tumors: Results Of The Somatostatin Treatment Experience Trial (STREET) - Ström T; Kozlovacki G; Myrenfors P; Almquist M (Patient Preference and Adherence, 2019)
Torbjörn Ström,1 Gordana Kozlovacki,2 Peter Myrenfors,1 Martin Almquist3 1Medical Department, Ipsen AB, Stockholm, Sweden; 2Department of Medical Sciences, Section of Endocrine Oncology, Uppsala University, Uppsala, Sweden; 3Department of Endocrine and Sarcoma Surgery, Lund University, Lund, SwedenCorrespondence: Martin AlmquistDepartment of Endocrine and Sarcoma Surgery, Lund University, Lund 221 85, SwedenTel +46 46 17 62 45Fax +46 46 14 72 98Email martin.almquist@med.lu.sePurpose: Evaluate patients’ and nurses’ experiences, including injection problem frequency, with the somatostatin analogues (SSAs) lanreotide autogel® (Somatuline® autogel®, deep subcutaneous) and octreotide long-acting release (LAR) (Sandostatin® LAR®, intramuscular) when treating gastroenteropancreatic neuroendocrine tumors (GEP-NETs).Methods: An observational, cross-sectional study across 2 NET centers in Sweden. Questionnaires based on participants’ most recent injection experience were sent to patients with GEP-NETs treated with octreotide or lanreotide, and to nurses administering these treatments. Nurses were identified via patients completing their questionnaires. Resource use was sourced from Swedish prescription registry records. The planned sample size was 200, based on an estimated proportion of 0.50 and ±7% precision.Results: 119/156 patients (n=53, lanreotide; n=66, octreotide) and 43/53 nurses (n=22, lanreotide; n=21, octreotide) completed questionnaires. Despite smaller recruitment than planned, the endpoint precision was ±9% with 119 participants, and still considered reasonable. More octreotide-treated patients reported problems (18% vs none; P=0.001) and experienced moderate-to-high anxiety pre-injection (11% vs 2%). Patients had similar physical HRQoL scores overall (Short Form-12 mean composite scores: physical: 39.4 vs 37.6; mental: 50.7 vs 49.6). The mean number of lanreotide and octreotide doses dispensed per year were 11.1 and 12.6, respectively (P<0.05). In the lanreotide group, 28% self-injected, while 29% were not aware they could self-inject. In the octreotide group, 3% self-injected and 73% were unaware of the availability of an SSA for self-injection. Most patients (61%) felt well-informed about their disease and treatment. Nurses were generally experienced and felt confident and well-informed about giving SSA injections; however, only 12% felt well-informed about the disease and treatment.Conclusion: Those treated with lanreotide reported fewer injection problems and experienced less pre-injection anxiety than those treated with octreotide. SSA choice did not appear to affect patients’ HRQoL. Some patients treated with octreotide were unaware of an SSA with the flexibility of self-injection.Keywords: gastroenteropancreatic neuroendocrine tumors, self-administration, somatostatin analogues